Fermentative characteristics and nutritional value of sugarcane silage added with two types of urea - Sousa-Alves, Wagner; Rigueira, João-Paulo S.; Almeida-Moura, Marielly M.; de-Jesus, Diego L. S.; Monção, Flávio P.; Rocha-Júnior, Vicente R.; Aspiazú, Ignácio; de-Jesus, Nathália G.; de-Melo, Jozélia A. R.; da-Silva, Marcos F. P. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Dry matter (DM) loss is high in sugarcane silage due to its high content of soluble carbohydrates which favors yeast growth and ethanol production, thus reducing the nutritional value of the preserved forage. Objective: To determine the effect of adding two types of urea at two concentration levels to sugarcane silage on the nutritional value and fermentative characteristics of the silage. Methods: A completely randomized 2×2+1 factorial design was used, based on two types of urea (conventional and protected), two urea concentration (0.5 and 1.0% of the natural matter), and a control (sugarcane silage with no additives). Six replicates were used. The mixture was placed in PVC silos and opened after 60 days. Results: There was no difference in DM content or effluent losses by the addition of urea. In regards to neutral detergent fiber, acid detergent fiber, and lignin, decreased levels were observed compared to the control, regardless of urea type. Urea type and concentration had an effect on ammoniacal nitrogen content, with higher values for conventional urea, but not affecting the pH. The addition of urea to sugarcane silage reduced gas losses and raised the levels of crude protein, ether extract, and effective degradability. Conclusion: Adding protected or conventional urea at 1% of natural matter at the time of sugarcane ensiling reduces gas losses and improves nutritional composition of the silage.